Heat transfer and fluid flow in biological processes - Becker, Sid M.; Kuznetsov, Andrey V. (London : Academic Press, an imprint of Elsevier, 2015)
Heat Transfer and Fluid Flow in Biological Processes covers emerging areas in fluid flow and heat transfer relevant to biosystems and medical technology. This book uses an interdisciplinary approach to provide a comprehensive prospective on biofluid mechanics and heat transfer advances and includes reviews of the most recent methods in modeling of flows in biological media, such as CFD. Written by internationally recognized researchers in the field, each chapter provides a strong introductory section that is useful to both readers currently in the field and readers interested in learning more about these areas. Heat Transfer and Fluid Flow in Biological Processes is an indispensable reference for professors, graduate students, professionals, and clinical researchers in the fields of biology, biomedical engineering, chemistry and medicine working on applications of fluid flow, heat transfer, and transport phenomena in biomedical technology.
Bioheat transfer and thermal heating for tumor treatment / Huang-Wen Huang, Tzyy-Leng Horng -- Tissue response to short pulse laser irradiation / Mohit Ganguly, Ryan O'Flaherty, Amir Sajjadi, Kunal Mitra -- Quantitative models of thermal damage to cells and tissues / Neil T. Wright -- Analytical bioheat transfer : solution development of the Pennes' model / Sid M. Becker -- Characterizing respiratory airflow and aerosol condensational growth in children and adults using an imaging-CFD approach / Jinxiang Xi, Xiuhua A. Si, Jong Won Kim -- Transport in the microbiome / R.J. Clarke -- A critical review of experimental and modeling research on the leftward flow leading to left-right symmetry breaking in the embryonic node / I. A. Kuznetsov, A. V. Kuznetsov -- Fluid-biofilm interactions in porous media / George E. Kapellos, Terpsichori S. Alexiou, Stavros Pavlou -- Flow through a permeable tube / C. Pozrikidis -- Transdermal drug delivery and percutaneous absorption : mathematical modeling perspectives / Filippo De Monte, Giuseppe Pontrelli, Sid M. Becker -- Mechanical stress induced blood trauma / Katharine Fraser -- Modeling of blood flow in stented coronary arteries / Claudio Chiastra, Francesco Migliavacca -- Hemodynamics in the developing cardiovascular system / C. Poelma, B. P. Hierck.
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed Jan. 15, 2015).
Elsevier
Keywords: Biological transport -- Mathematical models; Body fluid flow -- Mathematical models; Heat -- Physiological effect -- Mathematical models; SCIENCE / Life Sciences / Cell Biology; Biological transport -- Mathematical models; Body fluid flow -- Mathematical models; Heat -- Physiological effect -- Mathematical models; Electronic books; Electronic books